2008
DOI: 10.1111/j.1463-1318.2008.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and urinary dysfunction following rectal dissection compared with segmental colectomy

Abstract: More patients after rectal dissection vs segmental colectomy had urinary tract infections [15 (31%) vs 3 (17.5%), P = 0.04]. At 37 months, urinary dysfunction after rectal excision was seen in 29 (60%; 20 men) vs nine (37.5%; eight men) after segmental colectomy. Postoperative urinary symptoms were significant in group A, but not in group B (pre: vs post; groups A and B: poor stream--13%vs 38%, P = 0.001 and 21%vs 21%, P = NS; incontinence--4.2%vs 17%, P = 0.008 and 8%vs 8%, P = NS; hesitancy--13%vs 35%, P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 12 publications
0
32
1
Order By: Relevance
“…In another study, Quah et al 17 found a similar rate of erectile dysfunction, while 40% of men also reported an inability to ejaculate between 2 and 4 years after rectal excision. Among women, reported rates of dyspareunia vary from 6% at a median of 37 months after rectal excision 18 to more than 60% following abdominoperineal resection (APR) at a median of 52 months previously. 13 With respect to alterations in orgasm in women, rates range from 0% following segmental colectomy 18 to more than 30% following APR.…”
Section: Prevalence and Assesment Of Specific Sexual Dysfunctions In mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Quah et al 17 found a similar rate of erectile dysfunction, while 40% of men also reported an inability to ejaculate between 2 and 4 years after rectal excision. Among women, reported rates of dyspareunia vary from 6% at a median of 37 months after rectal excision 18 to more than 60% following abdominoperineal resection (APR) at a median of 52 months previously. 13 With respect to alterations in orgasm in women, rates range from 0% following segmental colectomy 18 to more than 30% following APR.…”
Section: Prevalence and Assesment Of Specific Sexual Dysfunctions In mentioning
confidence: 99%
“…Among women, reported rates of dyspareunia vary from 6% at a median of 37 months after rectal excision 18 to more than 60% following abdominoperineal resection (APR) at a median of 52 months previously. 13 With respect to alterations in orgasm in women, rates range from 0% following segmental colectomy 18 to more than 30% following APR. 13 In a recent study among male and female CRC survivors who had undergone colon or rectal resection at least 1 year previously, 20% of colon cancer survivors and 5% of rectal cancer survivors reported sexual problems related to reduced sexual desire.…”
Section: Prevalence and Assesment Of Specific Sexual Dysfunctions In mentioning
confidence: 99%
“…The increased risk of urinary dysfunction in RC patients has been reported in an earlier study with a small number of patients, which found that significantly more patients had urinary dysfunction after rectal resection than after segmental colectomy [19]. A few previous studies have been conducted in cohorts with more than 100 female patients with RC; all reported a correlation between treatment for RC and subsequent urinary dysfunction [5,7–10].…”
Section: Discussionmentioning
confidence: 94%
“…Partial colectomy performed surgically is the current standard treatment for McKittrick-Wheelock syndrome (MWS) [2,3]. However, its invasiveness and postoperative complications are sometimes problematic [4,5]. Moreover, if colostomy is required, the patient's quality of life is drastically reduced.…”
Section: Introductionmentioning
confidence: 99%